TINGKAT KECERDASAN ADVERSITY MAHASISWA PERANTAU DI MANADO - Aris Soleman (JIVA : Journal of Behavior and Mental Health, 2020)
ABSTRACTThe overseas students will experience and face many changes (shock culture). They have to face the new environment, culture, and systems. For this reason, the overseas students need a high level of struggle and endurance in facing and solving challenges and problems occured. The purpose of this study was to measure and describe the adversity intelligence of overseas students in Manado. This research used a descriptive research with a quantitative approach. The population of this research was the overseas students in Manado. Furthermore, the samples taken were 100 students by the sampling technique using Quota Sampling. The technique for analyzing data was done by using the Ms. Excel program. The results showed that the majority of respondents were at a moderate level of Adversity intelligence. There are no respondents who have a high level of Adversity intelligence.Keywords: Adversity Intelligence, the Overseas StudentsÂ ABSTRAK Mahasiswa perantau akan mengalami dan menghadapi banyak perubahan (shock culture). Mereka harus menghadapi lingkungan, budaya serta sistem yang baru. Untuk itu mahasiswa perantau membutuhkan daya juang serta daya tahan yang tinggi dalam menghadapi dan menyelesaikan tantangan dan permasalahan yang terjadi. Tujuan penelitian ini adalah untuk mengukur dan menggambarkan kecerdasan adversity mahasiswa perantau di kota Manado. Penelitian ini menggunakan tipe penelitian deskriptif dengan pendekatan kuantitatif. Populasi penelitian ini adalah mahasiswa perantau yang ada di kota Manado. Sedangkan sampel yang diambil adalah sebanyak 100 orang mahasiswa dengan teknik pengambilan sampel menggunakan Quota Sampling. Teknik untuk menganalisis data dilakukan dengan menggunakan program Ms. Excel. Hasil penelitian menunjukkan bahwa sebagian besar responden berada pada tingkat kecerdasan Adversity yang sedang. Tidak ada responden yang memiliki tingkat kecerdasan Adversity yang tinggi.Kata kunci: Kecerdasan Adversity, Mahasiswa Perantau